Het of Atworth's Purple Mountain - Levy, Audrey (Petits Propos Culinaires, 1999)
Summer pudding has developed into one of those subjects that runs and runs. See Notes and Queries in PPC 60 and 61. And there seems to be scope for further research, eg into the processes by which it mutated from Hydropathic, Rhode Island and Wakefield Pudding.